Antimicrobial Activity of Geobacillus thermoleovorans Ir1 Active Compounds against Pathogenic Bacteria - Mahdi, Mayaada S.; Ibrahim, Hiba K.; Al-ugaili, Dhafar N. (Iraqi Journal of Science, 2024)
It is necessary to follow new strategies for the isolation of bacteria with unique characteristics from novel sources during the search for new antimicrobial compounds. Geobacillus thermoleovorans strain Ir1 (JQ912239), a novel thermophilic bacterium, which was isolated from soil in Iraq (Basrah and Baghdad)    showed a good ability to utilize hydrocarbon compounds. This study objective was to demonstrate G. thermoleovorans Ir1 potential antibacterial capabilities. The ability of the spore-forming bacterium G. thermoleovorans Ir1 to produce antimicrobial bioactive compounds that affects two pathogenic bacteria Pseudomonas aeruginosa and Staphylococcus aureus was investigated. The zones of inhibition were 16 mm and 15mm respectively. Extracted bioactive compounds were identified using gas chromatography-mass spectrometry (GC-MS) analysis. The results showed that this strain inhibited the growth of the tested bacteria. The antimicrobial activity of the strain might be due to the combination between formamide and 2, 2-bis-(4-hydroxyphenyl)-butane compounds as prodrugs by comparing the gas chromatography-mass spectrometry analysis of the pure and mixed extracts.. Moreover, the filtrate of the thermophilic G. thermoleovorans Ir1 was examined for inhibition of biofilms formed by pathogenic bacteria, the results showed that the filtrate was able to inhibit the biofilms of P. aeruginosa, S. aureus, B. subtillus, K.  pneumonia, and E.  coli.. The results of this study are the first to record the  the production of these bioactive substances by the thermophilic G. thermoleovorans Ir1 at 65°C.